EVALUATION OF THE ANTICONVULSANT EFFECT OF AQUEOUS EXTRACT OF CENTELLA ASIATICA IN ALBINO MICE - Deka, Dipjyoti; Chakravarty, Pinaki; Purkayastha, Ayan (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To evaluate the antiepileptic activity of aqueous extract of Centella asciatica in maximal electroshock (MES) and pentylenetetrazole (PTZ) induced convulsions. Methods: The anticonvulsant activity of leaves of Centella asciatica (200 mg/kg and 400 mg/kg) in mice was assessed using MES and PTZ induced seizure models. Abolition of tonic hind limb extension (MES and PTZ) and increase in seizure latency (PTZ) when compared to control group, were taken as a measure of protection. Statistical analysis was done using one-way ANOVA followed by Tukey-Kramer multiple comparisons test. The test was considered to be significant at p<0.05. Results: The aqueous extract of Centella asiatica at a dose of 200 mg/kg has abolished tonic hind limb extension in 1 out of 6 animals in MES while there was no anticonvulsant action in PTZ convulsions. At a dose of 400 mg/kg body weight, the aqueous extract of Centella asiatica has shown a significant anticonvulsant effect against both MES and PTZ convulsions, where it has abolished tonic hind limb extension in 4 mice in MES method and in all 6 mices in PTZ method. Conclusion: The aqueous extract of Centella asiatica showed efficacy in both MES and PTZ convulsions in mice at a dose of 400 mg/kg. Since the clinical correlates of MES seizures are tonic-clonic convulsions and correlates of PTZ seizures are absence seizures, the aqueous extract of Centella asiatica is likely to be useful in the treatment of tonic-clonic and absence seizures.